2008
DOI: 10.4161/auto.5920
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis inhibition by Bcl-2 gives way to autophagy in glucocorticoid-treated lymphocytes

Abstract: Glucocorticosteroid hormones, including prednisone and dexamethasone (Dex), have been used to treat lymphoid malignancies for many years because they readily induce apoptosis in immature lymphocytes lacking Bcl-2. However, elevated expression of the anti-apoptotic protein Bcl-2 inhibits apoptosis and contributes to glucocorticoid resistance. Using the Bcl-2-negative WEHI7.2 lymphoma line as an experimental model, we found that Dex not only induces apoptosis but also induces autophagy. The caspase inhibitor Z-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…32 A recent publication, however, argues that autophagy induced by Dex in a mouse T cell leukemia cell line transfected with Bcl-2 has a protective effect on Dex-induced cells death. 33 This contradiction might be a result of a differential, cell type-specific response to Dex. Interestingly, in the presence of caspase inhibitors, the autophagic features were preserved, suggesting that autophagy induced by Dex occurs upstream of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 A recent publication, however, argues that autophagy induced by Dex in a mouse T cell leukemia cell line transfected with Bcl-2 has a protective effect on Dex-induced cells death. 33 This contradiction might be a result of a differential, cell type-specific response to Dex. Interestingly, in the presence of caspase inhibitors, the autophagic features were preserved, suggesting that autophagy induced by Dex occurs upstream of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the presence of caspase inhibitors, the autophagic features were preserved, suggesting that autophagy induced by Dex occurs upstream of apoptosis. 33 We have also attempted to address the important question of what are the signals delivered by Dex that trigger autophagy? An earlier study by our group has shown that Dex-treatment causes downregulation of the antiapoptotic Bcl-2 family members Bcl-2 and Bcl-XL at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was suggested that Bcl-2 and Bcl-xL enhance autophagy induced by an apoptotic insult (in Bax/Bak double-knockout cells that cannot undergo apoptosis) by upregulation of Beclin-1, and thereby mediate autophagy-dependent death (Shimizu et al, 2004;Swerdlow et al, 2008). More recently, different outcomes were observed: autophagy induction by glucocorticoid in T cells was dependent on the expression of Bcl-2 without detectable Beclin-1/Bcl-2 interactions, but with ensuing survival (Swerdlow et al, 2008), whereas in MCF7 cells with endogenous Beclin-1, knockdown of Bcl-2 increased autophagy and cell death (Akar et al, 2008). Further studies that take all the participating proteins into account are needed to establish whether these different mechanisms can be reconciled.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this autophagy induction is enhanced by Bcl-2 overexpression, apparently because of the inhibition of dexamethasoneinduced apoptosis. 45 Also, a recent publication shows that overexpressed Beclin 1 does not prevent the anti-apoptotic effect of Bcl-2. 46 This is consistent with the results that we have obtained in cells co-expressing Bcl-2 and Beclin 1-WT (see Figure 7b, blue bars).…”
Section: Discussionmentioning
confidence: 99%